Analisis Pertumbuhan Kartilago Epifisialis Os Tibia Fetus Mencit (Mus musculus L.) Swiss Webster Setelah Induksi Ochratoxin A Selama Periode Organogenesis - Arum Setiawan; Mammed Sagi; Widya Asmara; Istriyati Istriyati (Jurnal Biologi Papua, 2012)
The aims of this study were determined the effects of Ochratoxin A (OTA) on growth of fetus tibia epiphyseal cartilage during organogenesis period. Twenty four pregnant mice were divided randomly into 4 groups of 6. Ochratoxin A was dissolved in sodium bicarbonateand administered orally on seventh to fourteenth days of gestation at dosage of 0.5, 1.0, 1.5 mg/kg bw, respectively. The remaining were used as control. The fetal tibia was taken after the 18 th day of pregnancy. The growth of tibia epiphyseal cartilages were observed histologically using Erlich’s Haematoxylin-Eosin Stain. The result of this study indicated that OTA caused decreased thickness of the rest zone, proliferative zone, maturation zone and calsification zone of the fetus tibial growth plate significantly. Key words: Ochratoxin A, tibia, cartilage, and thickness.